A kind of γ-graphite monoacetylene nanosheet and preparation method thereof
By electrochemical peeling on the composite of γ-graphite monoalkyne crystal powder and liquid metal, high-quality γ-graphite monoalkyne nanosheets were successfully prepared, which solved the problems of complex preparation process, high cost and poor product crystallinity in the prior art, and achieved efficient and economical preparation of nanosheets.
Patent Information
- Application Number
- CN202411707393.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The prior art is difficult to efficiently prepare high-quality gamma-graphite monoalkyne nanosheets, and the preparation process is complex, the cost is high, and the product has poor crystallinity.
Halogenated benzene as the reaction monomer, and a catalyst was added to obtain a γ-graphite monoalkyne crystal powder, which was then mixed with a liquid metal, combined on a conductive substrate, and electrochemical peeling was performed through a three-electrode electrochemical system to successfully prepare γ-graphite monoalkyne nanosheets.
The preparation of high-quality γ-graphite monoalkyne nanosheets is achieved. The nanosheets are of nano-to-micron scale, with high purity, flat and uniform structure, excellent stability in air environment, simple and easy to use, low cost, and suitable for large-scale production.
Smart Images

Figure CN119461340B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of two-dimensional carbon material preparation, and in particular relates to a γ-graphite monoacetylene nanosheet and a preparation method thereof. Background Art
[0002] Graphyne has abundant carbon chemical bonds, a large conjugated system, wide interplanar spacing, excellent chemical stability, unique electronic structure and semiconductor properties. According to the number of ethynyl units between two adjacent aromatic rings, it can be divided into graphene monoacetylene (GY), graphene diacetylene (GDY), etc., and γ-graphene monoacetylene is the most stable structure in the Graphyne material family.
[0003] The current development history of γ-graphene is as follows: In 2010, the team of Academician Li Yuliang from the Institute of Chemistry, Chinese Academy of Sciences, synthesized a large-area graphene diyne film on a copper substrate for the first time through the Glaser-Hay coupling reaction, which made graphyne widely concerned by researchers (Chem. Commun., 2010, 46, 3256); in 2018, Cui et al. from Fudan University reported the successful synthesis of γ-graphene by ball milling CaC2 and PhBr6 using a mechanochemical method, but this method is an irreversible coupling reaction, the ball milling process is less controllable, and the quality and purity of the obtained γ-graphene are poor (Carbon, 2018, 136, 248-254); in 2020, Ding et al. used CaC2 and PhBr6 as precursors to synthesize γ-graphene by ultrasonic method, and the product also had the problem of poor crystallinity (Ultrasonics Sonochemistry, 2020, No. 2020); In 2022, Zhang et al. used the alkyne metathesis method to prepare γ-graphene, which can self-correct the structure during the polymerization process to achieve high crystallinity, but alkyne metathesis usually requires harsh reaction conditions and complex catalysts, and the process is complicated (Nat. Synth. 2022, 1, 449-454). At present, there are few reports on the preparation process of high-quality γ-graphene nanosheets. Summary of the invention
[0004] The present application discloses a γ-graphite monoacetylene nanosheet and a preparation method thereof, aiming to solve the technical problem of the existing blank in the preparation of high-quality γ-graphite monoacetylene nanosheets.
[0005] In order to achieve the above purpose, the technical solution of this application is:
[0006] The first aspect of the present application provides a method for preparing γ-graphite monoacetylene nanosheets, the preparation method comprising:
[0007] Using halogenated benzene as a reaction monomer, adding a catalyst and undergoing a coupling reaction, γ-graphite monoacetylene crystal powder is obtained;
[0008] The γ-graphite monoacetylene crystal powder is mixed with liquid metal and compounded on a conductive substrate to prepare a working electrode;
[0009] The working electrode, the counter electrode, the reference electrode and the electrolyte are assembled into a three-electrode electrochemical system for electrochemical stripping, and the precipitate is separated and collected to obtain the γ-graphite monoyne nanosheets.
[0010] In combination with the first aspect, preferably, the halogenated benzene is one of tribromobenzene, trifluorobenzene, triiodobenzene, trichlorobenzene, hexabromobenzene, hexafluorobenzene, hexaiodobenzene and hexachlorobenzene.
[0011] In combination with the first aspect, preferably, the catalyst is a copper catalyst, a palladium catalyst or a combination thereof.
[0012] In combination with the first aspect, preferably, the liquid metal is one of gallium indium tin liquid metal and gallium indium liquid metal, or a combination thereof.
[0013] In combination with the first aspect, preferably, the mass ratio of the γ-graphite monoyne crystal powder to the liquid metal is 0.5-10:1.
[0014] In combination with the first aspect, preferably, the material of the conductive substrate is one of copper, gold-plated silicon, gold and aluminum.
[0015] In combination with the first aspect, preferably, the electrolyte comprises a solvent and a cationic quaternary ammonium salt;
[0016] The solvent is one or more of N-methylpyrrolidone, N,N-dimethylformamide, acetonitrile, and dimethyl sulfoxide;
[0017] The cationic quaternary ammonium salt is one or more of tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetraheptylammonium bromide, tetramethylammonium fluoride, tetraethylammonium fluoride, tetrapropylammonium fluoride, tetrabutylammonium fluoride and tetraheptylammonium fluoride.
[0018] In combination with the first aspect, preferably, the mass concentration of the electrolyte is 2-10 mg / ml.
[0019] In combination with the first aspect, preferably, the counter electrode is made of platinum or carbon material;
[0020] The reference electrode is a silver chloride electrode or a non-mercury ion electrode.
[0021] The second aspect of the present application provides γ-graphene nanosheets prepared by the preparation method described in the first aspect.
[0022] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:
[0023] The preparation method provided in the present application exfoliates γ-graphite yne crystal powder by an electrochemical exfoliation method to achieve the successful preparation of γ-graphite yne nanosheets; on the one hand, the successful exfoliation preparation of high-quality γ-graphite yne nanosheets is achieved for the first time, and the prepared γ-graphite yne nanosheets have a size of nanometer to micrometer level, high purity and flat and uniform structure, and have excellent stability in an air environment; on the other hand, the preparation process is simple and easy, low cost, short preparation cycle, suitable for large-scale production, and has broad application prospects in catalysis, semiconductors, electronics, energy, environment and other aspects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 A physical picture of the γ-graphite monoacetylene crystal powder prepared in the examples of the present application;
[0026] Figure 2 TEM image of A1-γ-graphene monoacetylene nanosheets prepared in the examples of the present application;
[0027] Figure 3 This is an AFM image of the A1-γ-graphene monoacetylene nanosheet prepared in the embodiment of the present application;
[0028] Figure 4 This is an EDS image of the A1-γ-graphene nanosheets prepared in the examples of the present application. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0030] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0031] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0032] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0033] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0034] It should be noted that all raw materials and reagents in the examples of the present application were purchased on the market or prepared according to conventional methods well known to those skilled in the art.
[0035] In a first aspect, an embodiment of the present application provides a method for preparing γ-graphite monoacetylene nanosheets, the preparation method comprising:
[0036] Using halogenated benzene as a reaction monomer, adding a catalyst and undergoing a coupling reaction, γ-graphite monoacetylene crystal powder is obtained;
[0037] The γ-graphite monoacetylene crystal powder is mixed with liquid metal and compounded on a conductive substrate to prepare a working electrode;
[0038] The working electrode, the counter electrode, the reference electrode and the electrolyte are assembled into a three-electrode electrochemical system for electrochemical stripping, and the precipitate is separated and collected to obtain the γ-graphite monoyne nanosheets.
[0039] Among them, on the one hand, the successful exfoliation preparation of high-quality γ-graphene monoacetylene nanosheets was achieved for the first time, and the prepared γ-graphene monoacetylene nanosheets were of nanometer to micron size, high purity and flat and uniform structure, and had excellent stability in the air environment; on the other hand, the preparation process is simple and easy, low cost, short preparation cycle, suitable for large-scale production, and has broad application prospects in catalysis, semiconductors, electronics, energy, environment and other aspects.
[0040] It should be noted that γ-graphene monoacetylene crystal powder is obtained by using halogenated benzene as a reaction monomer, adding a catalyst, and coupling aromatic halide or alkenyl halide and terminal alkyne (Sonogashira coupling reaction) catalyzed by palladium. Graphene monoacetylene is composed of sp and sp 2 The lamellar porous structure composed of hybridized carbon atoms has a highly conjugated carbon material skeleton, alternating multi-level micropores and self-adjustable morphology. The structure of the prepared γ-graphene is shown in Formula 1:
[0041]
[0042] In the embodiment of the present application, the halogenated benzene is preferably one of tribromobenzene, trifluorobenzene, triiodobenzene, trichlorobenzene, hexabromobenzene, hexafluorobenzene, hexaiodobenzene and hexachlorobenzene. Among them, these halogenated benzenes all have a highly symmetrical structure, have higher selectivity and efficiency through the Sonogashira coupling reaction, and can form a structurally stable γ-graphite monoyne crystal powder.
[0043] In the embodiments of the present application, the catalyst is a copper catalyst, a palladium catalyst or a combination thereof. The selection of these catalysts can promote the occurrence of the Sonogashira coupling reaction and significantly reduce the reaction temperature and reaction time.
[0044] In the embodiment of the present application, the liquid metal is one of gallium indium tin liquid metal, gallium indium liquid metal or a combination thereof. Among them, these liquid metals have excellent conductivity due to the abundant presence of free electrons inside, because the conductivity of γ-graphite monoacetylene crystal powder is relatively weak. The working electrode made by the composite of liquid metal and γ-graphite monoacetylene crystal powder improves the electron transfer rate between the electrode and the electrolyte, and can quickly transfer electrons from the electrode to the electrolyte, thereby accelerating the rate of electrochemical reaction and increasing the generation yield of nanosheets during the stripping process.
[0045] In the embodiment of the present application, the mass ratio of the γ-graphite monoacetylene crystal powder to the liquid metal is preferably 0.5-10: 1. By controlling the mass ratio of the γ-graphite monoacetylene crystal powder to the liquid metal, the conductivity of the working electrode can be effectively controlled, thereby effectively controlling the reaction rate, efficiency and stability in the electrochemical reaction.
[0046] It should be noted that during the electrochemical stripping process, the liquid metal in the working electrode will strip the γ-graphite crystals once. After the stripped crystals fall onto the conductive substrate, they are stripped a second time, making the entire stripping process more complete and making the lamellar structure of γ-graphite smooth and uniform, with a size ranging from nanometers to micrometers.
[0047] It should be noted that the present application mixes the γ-graphite monoacetylene crystal powder with liquid metal, composites it on a conductive substrate, and prepares a working electrode. The present application does not specifically limit the composite method. The present application adopts a method for preparing a working electrode including: mixing the γ-graphite monoacetylene crystal powder with liquid metal, applying it on a conductive substrate, and obtaining a working electrode. Alternatively, the γ-graphite monoacetylene crystal powder is mixed with liquid metal, and then placed in a conductive mesh uncovered square box to obtain a working electrode.
[0048] In the embodiment of the present application, the material of the conductive substrate is one of copper, gold-plated silicon, gold, and aluminum. Among them, these conductive substrate materials have excellent mechanical and chemical stability and can provide a stable test environment and support.
[0049] In the embodiment of the present application, the electrolyte includes a solvent and a cationic quaternary ammonium salt; the solvent is preferably one or more of N-methylpyrrolidone, N,N-dimethylformamide, acetonitrile, and dimethyl sulfoxide; the cationic quaternary ammonium salt is preferably one or more of tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetraheptylammonium bromide, tetramethylammonium fluoride, tetraethylammonium fluoride, tetrapropylammonium fluoride, tetrabutylammonium fluoride, and tetraheptylammonium fluoride; the mass concentration of the electrolyte is preferably 2-10 mg / ml. Among them, the surface tension of these solvents is 10-100 mN / m, and they have affinity for γ-graphite monoacetylene nanosheets. By selecting these cationic quaternary ammonium salts as electrolytes, dissolving them in the solvent, under the action of an applied voltage, the quaternary ammonium cations migrate to the working electrode and embed into the interlayer of the γ-graphite monoacetylene crystals, which is conducive to the peeling of the γ-graphite monoacetylene crystals.
[0050] In the embodiment of the present application, the counter electrode is platinum or carbon material; the reference electrode is a silver chloride electrode or a non-mercury ion electrode. The counter electrode acts as an electron acceptor in the electrochemical reaction and participates in the reaction to ensure that the reaction on the working electrode is not disturbed. The reference electrode serves as a reference for comparison and as a benchmark for potential measurement, its electrode potential remains constant and does not change with the activity or concentration of the ion to be measured in the solution.
[0051] In the second aspect, the embodiments of the present application also provide γ-graphite nanosheets prepared by the preparation method described in the first aspect, so that the prepared γ-graphite nanosheets have high-quality structural characteristics and excellent structural stability, and have broad application prospects in catalysis, semiconductors, electronics, energy, environment and other aspects.
[0052] The technical solution of the present application will be further described below in conjunction with specific embodiments.
[0053] Example 1
[0054] This embodiment provides a method for preparing Al-γ-graphene monoacetylene nanosheets, which specifically includes:
[0055] S101: using tribromobenzene as a reaction monomer, adding cuprous iodide and tetrakistriphenylphosphine palladium to undergo a Sonogashira coupling reaction to obtain γ-graphite monoacetylene crystal powder;
[0056] S102: Weigh 10 mg of γ-graphite monoacetylene crystal powder and 10 mg of Ga 69 In 22 The Sn9 liquid metal was stirred and mixed for 30 min and coated on a 1*1CM copper sheet as a working electrode;
[0057] S103: A three-electrode electrochemical system was assembled using a graphite rod as a counter electrode and a non-mercury electrode as a reference electrode. The electrolyte was a 5 mg / ml tetraheptylammonium fluoride solution in N,N-dimethylformamide. The stripping voltage was -5 V and the time was 30 min. The stripped electrolyte mixture was centrifuged and the precipitate was washed with anhydrous ethanol by centrifugation. The process was repeated several times at a centrifugal speed of 15,000 rpm and a centrifugal time of 5 min to obtain A1-γ-graphene monoacetylene nanosheets.
[0058] Example 2
[0059] This embodiment provides a method for preparing A2-γ-graphene monoacetylene nanosheets, which specifically includes:
[0060] S201: Hexabromobenzene is used as a reaction monomer, and cuprous iodide is added to undergo a Sonogashira coupling reaction to obtain γ-graphite monoacetylene crystal powder;
[0061] S202: Weigh 5 mg of γ-graphite monoacetylene crystal powder and 10 mg of Ga 69 In 22 The Sn9 liquid metal was stirred and mixed for 30 minutes and placed in a copper square box as a working electrode;
[0062] S203: A three-electrode electrochemical system was assembled using a graphite rod as a counter electrode and a non-mercury electrode as a reference electrode. The electrolyte was a 5 mg / ml tetraheptylammonium fluoride solution in N,N-dimethylformamide. The stripping voltage was -10 V and the time was 30 min. The stripped electrolyte mixture was centrifuged and the precipitate was washed with anhydrous ethanol by centrifugation. The process was repeated several times at a centrifugal speed of 15,000 rpm and a centrifugal time of 5 min to obtain A2-γ-graphite monoacetylene nanosheets.
[0063] Example 3
[0064] This embodiment provides a method for preparing A3-γ-graphene monoacetylene nanosheets, which specifically includes:
[0065] S301: using hexabromobenzene as a reaction monomer, adding tetrakistriphenylphosphine palladium to undergo a Sonogashira coupling reaction to obtain γ-graphite monoacetylene crystal powder;
[0066] S302: Weigh 10 mg of γ-graphite monoacetylene crystal powder and 1 mg of Ga 69 In 22 The Sn9 liquid metal was stirred and mixed for 30 min and coated on a 1*1CM gold-coated silicon wafer as a working electrode;
[0067] S303: A three-electrode electrochemical system was assembled using a graphite rod as a counter electrode and a non-mercury electrode as a reference electrode. The electrolyte was a 5 mg / ml tetraheptylammonium fluoride solution in N,N-dimethylformamide. The stripping voltage was -10 V and the time was 30 min. The stripped electrolyte mixture was centrifuged and the precipitate was washed with anhydrous ethanol by centrifugation. The process was repeated several times. The centrifugal speed was 15000 rpm and the centrifugal time was 5 min to obtain A3-γ-graphite monoacetylene nanosheets.
[0068] In order to verify the structural characteristics of the γ-graphite monoacetylene nanosheets prepared in the examples of the present application, the γ-graphite monoacetylene nanosheets prepared in the examples were subjected to structural tests. The test results are as follows: Figure 1-4 As shown. Among them, Figure 1 This is a physical picture of γ-graphite monoyne crystal powder; Figure 2 TEM image of A1-γ-graphene monoacetylene nanosheets; Figure 3 AFM image of A1-γ-graphene nanosheets; Figure 4 This is the EDS image of A1-γ-graphene nanosheets.
[0069] according to Figure 1 As known, the actual picture of the γ-graphite monoyne crystal powder prepared in the embodiment of the present application is in the form of black powder.
[0070] according to Figure 2 As is known, the Al-γ-graphene monoacetylene nanosheets successfully prepared by the present application by an electrochemical exfoliation method clearly exhibit a sheet-like structure.
[0071] according to Figure 3 As known, the Al-γ-graphene nanosheets prepared in the present application clearly present a sheet-like structure, which is flat and uniform, and the average thickness of the layered structure is about 4.35 nm.
[0072] according to Figure 4As is known, the X-ray photoelectron energy spectrum of the A1-γ-graphene monoacetylene nanosheets prepared in the embodiment of the present application shows that carbon atoms account for 90.27%, the material is mainly composed of carbon atoms, oxygen atoms come from air adsorption, and other atoms come from the influence of the reaction process and will not affect the structure of the γ-graphene monoacetylene nanosheets.
[0073] Therefore, the preparation method provided in the present application exfoliates γ-graphite crystalline powder by electrochemical exfoliation to achieve the successful preparation of γ-graphite crystalline powder nanosheets, giving them high-quality structural characteristics and excellent structural stability, with a size of nanometer to micrometer. At the same time, the preparation process is simple and easy, low cost, short preparation cycle, suitable for large-scale production, and has broad application prospects in catalysis, semiconductors, electronics, energy, environment and other aspects.
[0074] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0075] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.
Claims
1. A method for preparing γ-graphite monoacetylene nanosheets, characterized in that: The preparation method comprises: Using halogenated benzene as a reaction monomer, adding a catalyst and undergoing a coupling reaction, γ-graphite monoacetylene crystal powder is obtained; The γ-graphite monoacetylene crystal powder is mixed with liquid metal and compounded on a conductive substrate to prepare a working electrode; The working electrode, the counter electrode, the reference electrode and the electrolyte are assembled into a three-electrode electrochemical system for electrochemical stripping, and the precipitate is separated and collected to obtain the γ-graphite monoyne nanosheets.
2. The preparation method according to claim 1, characterized in that: The halogenated benzene is one or more of tribromobenzene, trifluorobenzene, triiodobenzene, trichlorobenzene, hexabromobenzene, hexafluorobenzene, hexaiodobenzene and hexachlorobenzene.
3. The preparation method according to claim 1, characterized in that: The catalyst is a copper catalyst, a palladium catalyst or a combination thereof.
4. The preparation method according to claim 1, characterized in that: The liquid metal is one of gallium indium tin liquid metal and gallium indium liquid metal, or a combination thereof.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the γ-graphite monoacetylene crystal powder to the liquid metal is 0.5-10:
1.
6. The preparation method according to claim 1, characterized in that: The material of the conductive substrate is one of copper, gold-plated silicon, gold and aluminum.
7. The preparation method according to claim 1, characterized in that: The electrolyte includes a solvent and a cationic quaternary ammonium salt; The solvent is one or more of N-methylpyrrolidone, N,N-dimethylformamide, acetonitrile, and dimethyl sulfoxide; The cationic quaternary ammonium salt is one or more of tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tetraheptylammonium bromide, tetramethylammonium fluoride, tetraethylammonium fluoride, tetrapropylammonium fluoride, tetrabutylammonium fluoride and tetraheptylammonium fluoride.
8. The preparation method according to claim 7, characterized in that: The mass concentration of the electrolyte is 2-10 mg / ml.
9. The preparation method according to claim 1, characterized in that: The counter electrode is made of platinum or carbon material; The reference electrode is a silver chloride electrode or a non-mercury ion electrode.
10. A γ-graphene nanosheet prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing gamma graphite single acetylene carbon nanomaterial based on benzene precursor
CN108946698A
Preparation method of plasma fluorine-doped modified gamma-type graphite single alkyne carbon material
CN113104838A